Human and Mouse CD8+CD25+FOXP3+ Regulatory T Cells at Steady State and during Interleukin-2 Therapy - Churlaud, Guillaume; Pitoiset, Fabien; Jebbawi, Fadi; Lorenzon, Roberta; Bellier, Bertrand; Rosenzwajg, Michelle; Klatzmann, David (Frontiers in Immunology, 2015)
In addition to CD4+ regulatory T cells (Tregs), CD8+ suppressor T cells are emerging as an important subset of regulatory T cells. Diverse populations of CD8+ T cells with suppressive activities have been described. Among them, a small population of CD8+CD25+FOXP3+ T cells is found both in mice and humans. In contrast to thymic-derived CD4+CD25+FOXP3+ Tregs, their origin and their role in the pathophysiology of autoimmune diseases (AIDs) are less understood. We report here the number, phenotype, and function of CD8+ Tregs cells in mice and humans, at the steady state and in response to low-dose interleukin-2 (IL-2). CD8+ Tregs represent approximately 0.4 and 0.1% of peripheral blood T cells in healthy humans and mice, respectively. In mice, their frequencies are quite similar in lymph nodes (LNs) and the spleen, but two to threefold higher in Peyer patches and mesenteric LNs. CD8+ Tregs express low levels of CD127. CD8+ Tregs express more activation or proliferation markers such as CTLA-4, ICOS, and Ki-67 than other CD8+ T cells. In vitro, they suppress effector T cell proliferation as well as or even better than CD4+ Tregs. Owing to constitutive expression of CD25, CD8+ Tregs are 20- to 40-fold more sensitive to in vitro IL-2 stimulation than CD8+ effector T cells, but 2–4 times less than CD4+ Tregs. Nevertheless, low-dose IL-2 dramatically expands and activates CD8+ Tregs even more than CD4+ Tregs, in mice and humans. Further studies are warranted to fully appreciate the clinical relevance of CD8+ Tregs in AIDs and the efficacy of IL-2 treatment.